Tasas de crecimiento y diversidad de especies en relación a la dinámica del bosque primario de la reserva ecológica Mache Chindul. Periodo 1996-2016 - Feijoo Gómez, Augusto Guillermo (2016)
The research describes the growth rates and forest species diversity Biological Station Bilsa, in the area of influence of the Ecological Reserve Mache Chindul, Quinindé province of Esmeraldas. The contribution of volunteers Jatun Sacha Foundation allowed the gathering of information in 25 permanent sampling subplots during the period 1996 - 2016. 723 individuals, 83 species and 36 families were recorded. The results revealed that species diversity indices of Simpson and Shannon were 0.9386 and 3.4400 respectively. In addition, it was possible to establish the rate of importance value of species with the greatest ecological which weight were: Otoba gordoniifolia, Licania celiae, Iriartea deltoid, Bauhinia, Chlorocardium venenosum and Coussarea latifolia, like horizontal forest structure under study. The basal area was 13,740 m² / ha; Bauhinia species standing out with a value of 12,394 relative dominance. The growth of tree species is ecologically elemental to infer future on performance and improvement of forest products.